PENGARUH FAKTOR-FAKTOR TERTENTU TERHADAP FRAUDULENT FINANCIAL STATEMENT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Clarissa Felicia, Hendang Tanusdjaja (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to examine the influence of asset turnover ratio, financial stability, financial targets and profitability towards fraudulent financial statements in manufacturing companies listed on Indonesia Stock Exchange in periode of 2016-2018. This research is conducted by using 20 samples of manufacturing companies listed on Indonesia Stock Exchange. Data analysis was performed with descriptive statistics and hypothesis testing of regression method using SPSS Statistics 25. The results of this research shows that asset turnover ratio and financial stability have a significant negative effect towards fraudulent financial statements. Financial targets has significant positive effect towards fraudulent financial statements while profitability has positive effect on fraudulent financial statements.